2021
DOI: 10.1016/j.ajhg.2021.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Missense variants in DPYSL5 cause a neurodevelopmental disorder with corpus callosum agenesis and cerebellar abnormalities

Abstract: Re i ed Ma c iClick here to ie linked References

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 35 publications
0
27
0
Order By: Relevance
“…However, our analyses indicate a much stronger enrichment for the cortico-striatum circuitries (Figure 2D - E). DPYSL5 belongs to the collapsin response mediator protein (CRMP) family, and was implicated specifically with axonal growth by converging evidence from case studies 32 , molecular mapping 33 , and animal studies 34 . Interestingly, all CRMP family proteins shows association signals more evidently with ND ( Dpysl2 , p = 1.3e-14; Dpysl3 , p = 9e-7; Dpysl4 , p = 5e-8).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, our analyses indicate a much stronger enrichment for the cortico-striatum circuitries (Figure 2D - E). DPYSL5 belongs to the collapsin response mediator protein (CRMP) family, and was implicated specifically with axonal growth by converging evidence from case studies 32 , molecular mapping 33 , and animal studies 34 . Interestingly, all CRMP family proteins shows association signals more evidently with ND ( Dpysl2 , p = 1.3e-14; Dpysl3 , p = 9e-7; Dpysl4 , p = 5e-8).…”
Section: Resultsmentioning
confidence: 99%
“…Instead of cortical surface, our whole-brain multivariate GWAS indicates the effect sizes were more diffusely distributed among white matter tracts, especially within cortico-striatal circuitry (Figure 3g, 3h, Supplementary Table 7). DPYSL5 belongs to the collapsin response mediator protein (CRMP) family, including DPYSL2 , DPYSL3 , and DPYSL4 , which are essential for axonal growth and neurite morphogenesis 4749 (Figure 3i). Indeed, all tagged SNPs of the CRMP family proteins show stronger association signals with ND than with N0 and NF (Figure 3j).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Abnormal neurite outgrowth may cause aberrant polarity, abnormal synaptic plasticity of neuronal cells, and damage to axons and dendrites. Unusual neurodevelopment can induce autism, hyperactivity disorder, dyslexia and so on ( 40 ). Deformed neuronal cell morphology may also cause neurodegenerative diseases such as Alzheimer's disease and Parkinson's disease.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Jeanne et al reported nine patients, including one patient from the first family reported by Ritscher et al, and identified missense variants in DPYSL5 [ 45 , 46 ]. A recurrent de novo p.Glu41Lys was found in eight unrelated patients, while a p.Gly47Arg was identified in one patient from the original RSS family.…”
Section: Human Disorders Associated With Retriever Dysfunctionmentioning
confidence: 99%